ANALISIS INDIKATOR PENYUSUN VARIABEL LATEN YANG MEMPENGARUHI KINERJA PEMASARAN TENUN KRE’ ALANG - Sofya, Nora Dery; Ekastini, Ekastini; Hermanto, Koko (LPPM Institut Pendidikan Nusantara Global, 2023)
Before knowing the factors that influence competitive advantage and marketing performance of Kre' Alang weaving, it must first determine the indicators that have a relationship with the latent variables. The method used to analyze this is confirmatory factor analysis. This method is used to provide information whether the model that has been modeled is in accordance with the hypothesis that has been formulated. The results of the study show that the latent variables for technology orientation are composed by the use of the latest technology, accelerating service to customers, supporting the innovation process, and ease of operationalization. Product innovation latent variables are composed by indicators of duplication and synthesis. Competitive advantage latent variables are composed by product uniqueness indicators. While marketing performance variables are composed by indicators of financial performance, operational performance, and market-based performance. The test results of the confirmatory factor model of the marketing performance of Kre' Alang woven fabric which were compiled were valid and reliable.